Analisis Kesenjangan Upah Pekerja Penyandang Disabilitas dan Non Disabilitas di Jabodetabek Tahun 2022 - Ningrum, Citra Dian; Rini, Ariska Nurfajar (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2024)
This study aims to analyze the magnitude of the wage gap between disabled and non-disabled workers in Jabodetabek in 2022 using the Ordinary Least Squares (OLS) and Oaxaca-Blinder Decomposition methods. The data used in this study are derived from the National Labor Force Survey (SAKERNAS). The results of the study show that, in general, workers with disability status are negatively and significantly associated with wages, indicating that the wages received by disabled workers are 6.32% lower than those of non-disabled workers. The OLS regression results are further complemented by the Oaxaca-Blinder Decomposition method to analyze the magnitude of the average wage gap between disabled and non-disabled workers. The results reveal a wage gap of 34.2%, as indicated by the difference coefficient (D). Of this gap, 27.9% can be explained by differences in the socioeconomic characteristics of workers, while the remaining 6.32% is attributable to unexplained or unobserved factors.